Chinese tourist preferences for nature based destinations: a choice experiment analysis - Jiong Yan; Jan Barkmann; Rainer Marggraf (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2007)
This paper used a choice experiment (CE) method to investigate Chinese middle class tourist preferences for nature based destinations in southwestern China. Interview data from 616 respondents presented that in general, the respondents preferred natural based destinations in southwestern China with more features of convenience, cultural and natural attractions, but less tarnished nature experiences, sustainable tourism services and cost. The effect coded models revealed in further details that the developed convenience level, the magnificent natural attractions and original cultural attractions were most preferred by the respondents. Though the general negative impact of tarnished nature experiences on destination preference, it was not the pure wilderness, but the mixture of naturalness and basic infrastructures, and occasional other visitors, were mostly welcomed by the respondents. The limited sustainable tourism services got modest positive appreciation but the extensive sustainable tourism services level was not preferred by the respondents.
Keywords: 330; preference; choice experiment; Chinese middle class tourists; nature based destinations; southwestern China; Urlaubsverhalten; Chinesen; Erholungsgebiet; Öko-Tourismus; Willingness to pay; China